Dengue cases in Brazil: Evolution of reported cases in the last 10 years (Research, Society and Development, 2024)
Objective: The present study focused on describing the occurrence of Dengue cases in Brazil in the last ten years. Methodology: Observational epidemiological study of the time series analysis type, being carried out by collecting data from the period between 2014-2023 in Brazil, about reported cases of Dengue in Brazil, using registry data from the Notifiable Diseases Information System (SINAN) within the Department of Information and IT of the Unified Health System (DATASUS), having the following variables: Year of Notification. Results and Discussion: Between the years researched, there were approximately 9,710,271 reported cases of Dengue in Brazil, with 2015 being the year with the highest occurrence with 1,709,099 (17.60%) registered individuals, followed by 2019 (1,553,504 – 15.99%), 2023 (1,508,653 – 15.53%), 2016 (1,497,865 - %15.42), 2022 (1,393,994 – 14.35%), 2020 (944,502 – 9.72 %), 2014 (591,514 – 6.09%), 2021 (531,935 – 5.47%), 2018 (269,275 – 2.77%) and 2017 (241,865 – 2.49%). Conclusion: Epidemiological surveillance is essential to detect dengue outbreaks early and implement effective control measures. Integrating climate, behavioral and public health data can improve responses to this threat. Effective public policies, associated with awareness campaigns and community mobilization, are essential to reduce the incidence of dengue. Continuous surveillance and scientific research must be priorities to mitigate the impacts of dengue and protect the health of the Brazilian population.